CARACTERIZACIÓN DE LOS AZÚCARES PRESENTES EN EL MUCÍLAGO DE CACAO (Theobroma cacao L), OBTENIDOS MEDIANTE HIDRODESTILACIÓN - PEÑAFIEL HIDALGO, SANDRA ISABEL (2025)
This research focused on the impact of temperature on the concentration of sugars present in cocoa mucilage, specifically in the CCN-51 and Nacional varieties